External damp environment aggravates diarrhea in spleen deficiency and dampness syndrome in mice: involvement of small intestinal contents microbiota, energy metabolism, gastrointestinal and fluid functions - Yu, Donglin; Xie, Shiqin; Guo, Mingmin; Wu, Yi; Tian, Qianghong; Wang, Zhiyan; Zhou, Sainan; Cai, Ying (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectivesRecent studies have increasingly demonstrated that a multiplatform water environment combined with lard gavage is an effective method for establishing a mouse model of diarrhea. However, the interactions between intestinal microorganisms and diarrhea, as well as the relationships among energy metabolism, fluid balance, and gastrointestinal function in this model, remain poorly understood.MethodsBuilding on previous research, this study aimed to optimiz and replicate a multiplatform water environment combined with a lard gavage model. Male Kunming mice, free of specific pathogens, were randomly divided into four groups: a normal control group (ZC), a standing group (ZL), a standing combined with lard group (ZLZ), and a standing combined with internal and external wet conditions group (ZLZS). The mice in the ZL, ZLZ, and ZLZS groups were subjected to 4 hours of daily standing in a custom-designed multiplatform water environment. Starting on day 8, mice in the ZLZ and ZLZS groups were gavaged with lard (0.4 mL per session, twice daily) for 7 consecutive days, while those in the ZLZS group were additionally exposed to a wet litter environment (50 g/100 mL). The ZC and ZL groups received equal volumes of sterile water via gavage. The microbiota in the small intestine, as well as serum levels of cAMP, cGMP, VIP, Gas, and D-xylose, were analyzed.ResultsCompared with the ZLZ group, the ZLZS group showed significantly lower serum levels of cAMP/cGMP (p<0.01) and Gas (p<0.01). D-xylose levels were lower in the ZL, ZLZ, and ZLZS groups compared to the ZC group, while VIP levels were significantly higher in the ZL and ZLZS groups (p<0.01). Moverover, Corynebacterium, Empedobacter, and Pseudochrobactrum were identified as characteristic bacterial genera in the ZLZS group. The mechanism by which the small intestinal microbiota induces diarrhea was linked to the biosynthesis of secondary bile acids.ConclusionA multiplatform water environment combined with lard gavage can effectively induce diarrhea, and the addition of an external wet environment exacerbates this condition by affecting small intestinal contents microbiota and other functions.